Darivanje kruhom u običajima Hrvata - Svirac, Manda (Zagreb : Družina, 1998)
Résumé
Summary
Zusammenfassung
Str.7-8: Proslov / Ćiril Kos
Bibliografija: str. 121-132
Keywords: kruh; žitarice; običaji; Hrvati; narodni običaji; Hrvatska